Precedent in Islamic Law with Special Reference to the Federal Shariat Court and the Legal System in Pakistan - Munir, Muhammad (Islamic Studies, 2008)
This paper attempts to answer the question whether the common law doctrine of precedent as practiced in Pakistan is compatible with the traditional Islamic legal system. The paper examines the role of the principles of Islamic law in the Pakistani legal system and focuses on the role of the Federal Shariat Court and the binding status of its decisions. The paper also examines the prevalent practice of courts in Saudi Arabia and finds that judges there are not bound by the decisions of the higher courts. Those who oppose the doctrine of precedent generally argue that this doctrine restricts judges from undertaking ijtihād and that it is against the principle of independence of judiciary. However, the supporters of precedent argue that the doctrine ensures uniformity and analytical consistency in the legal system. It concludes that the practice of binding precedent under Articles 189, 201 and 203 GG of the 1973 Constitution is "institutionalized taqlīd" and that there is little, if any, material about the role of precedent in Islamic law.